Development Of Contextual Teaching Materials Using A Sports Context In Statistics For Sports-Talented Schools Nusa Tenggara Timur Province - Boleng, Yasinta Christanti; Rudhito, Marcellinus Andy (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
At Nusa Tenggara Timur Provincial Sports Gifted High School in Kupang show that there are still many students who are not enthusiastic about learning mathematics in class. On every occasion, learning mathematics should start with the identification of problems that are appropriate to the situation (contextual problems). With the application of contextual problems, using real examples related to everyday life will bring students to conditions that can make students actively involved in learning. This research aims to produce contextual teaching materials on statistics material with a sports context for students at Sports Gifted Schools, as well as describe the impact on student learning outcomes from the results of developing these teaching materials. The development model that will be used to develop learning tools in this research is the ADDIE model. Data collection uses validation sheets, student response questionnaires to teaching materials, and student learning outcomes tests. Based on the results of the research, teaching materials in the form of statistical material modules measuring data concentration using the context of middle-distance running sports were declared valid and suitable for use, with the assessment results from material expert validators being 76% valid and the assessment results from media expert validators being 88% very valid. The teaching materials also received a good response from students, with the results of the student questionnaire responding to the teaching materials at the small group trial stage getting a percentage of 91% and at the large group trial stage getting a percentage of 95%. The teaching materials developed also have a positive impact on student learning outcomes. This can be seen from the results of students' learning tests after using these teaching materials, where the overall average score of students is 78.1, and the percentage of completeness obtained is 70%. Apart from that, it can also be seen that in the learning process, the students are actively discussing.